(untitled) (Research, Society and Development, 2025)
This study aimed to review the literature on Mycoplasma and Ureaplasma colonization in pregnant women and its association with obstetric and neonatal complications. The systematic review followed the PRISMA guidelines, including studies published between 2014 and 2024 in the PUBMED/MEDLINE, WPRIM, LILACS, and IBECS databases. A total of 60 publications investigating the presence of M. hominis, M. genitalium, U. urealyticum, and U. parvum and their relationship with adverse obstetric outcomes and neonatal complications were selected. The results indicated that Mycoplasma colonization in pregnant women varies according to the studied population, the type of sample collected, and the diagnostic methodology used. Many studies found a positive association between Mollicutes colonization and preterm birth, miscarriage, premature rupture of membranes, chorioamnionitis, and other adverse pregnancy outcomes. Ureaplasma spp. was the most frequently detected species, being associated with intrauterine inflammation and prematurity. The presence of these microorganisms in amniotic fluid and placenta was correlated with adverse neonatal outcomes, including respiratory distress syndrome and bronchopulmonary dysplasia. Although evidence suggests a potential pathogenic role of Mycoplasma in pregnancy, the heterogeneity of studies prevents definitive conclusions regarding its isolated influence or in combination with other microorganisms on pregnancy outcomes. Prospective studies are needed to analyze Mycoplasma colonization within the context of the gestational vaginal microbiome, considering epidemiological and clinical factors to better understand its impact on pregnancy.